Kreatifitas Patchwork Perca Batik Dayak Sebagai Upaya Menumbuhkan Jiwa Entrepreneurship Komunitas Perempuan Gereja Gloria Kuala Kapuas - Tiawon, Harin; Widati, Titiani; Heriamariaty, Heriamariaty; Amiany, Amiany; Angelica, Novelia Putri (Diteksi : Jurnal Pengabdian Kepada Masyarakat, 2024)
Selat Barat Village is one of the residential areas that has many women's community groups that are active in social and religious activities, one of which is the SPPer Gloria Church Group. This group is one of the largest Christian social religious activity drivers in this area which involves many productive-age housewives between 30-46 years old who are educated on average high school who have a lot of free time. The existence of this creative craft industry can be a solution in efforts to foster an entrepreneurial spirit and improve the economy of the area. The potential of the Dayak batik patchwork home industry as a creative and innovative craft product can be a solution in increasing the income level and welfare of the community in Selat Barat Village by producing products with minimal capital and high selling power in the Kuala Kapuas City area. In addition, there has never been this art craft in the Central Kalimantan Province in particular. Therefore, it is necessary to provide training activities to make creative patchwork products. These creative patchwork activities include: (1) preparation, namely preparing training modules, basic knowledge of patchwork art trials; (2) implementation of training: making patterns, printing patterns onto fabric, cutting and joining, sewing or joining; (3) evaluation. The results of the training are making innovative interior design craft products including tablecloths, chair cushion covers, flower pot coasters, doormats and wallets.